Soil test-based nutrient balancing improved crop productivity and rural livelihoods: Case study from rainfed semi-arid tropics in Andhra Pradesh, India - Chander, G.; Wani, S.P.; Sahrawat, Kanwar Lal; Dixit, S.; Venkateswarlu, B.; Rajesh, C.; Rao, P.R.; Pardhasaradhi, G. (Informa UK Limited, 2014)
Widespread multinutrient deficiencies in the semi-arid tropics (SAT) are among major factors for large gaps between farmers’ current crop yields and potential yields. In this study, we adopted a stratified soil sampling method to assess soil fertility-related constraints in farmers’ fields in eight districts of Andhra Pradesh in the semi-arid tropics of India. Most of the fields across all eight districts were critical in sulfur (61%–98% deficient fields); and up to six districts each in boron (83%–98% deficient fields), zinc (50–85% deficient fields), and soil organic carbon (55–97% deficient fields). Low soil organic carbon specifically indicates nitrogen deficiency. Phosphorus deficiency was critical in three districts (60–84%) while potassium in general was adequate. Soil test-based nutrient balancing through the application of sulfur, boron, and zinc in addition to farmers’ practice of adding only nitrogen, phosphorus, and potassium increased crop productivity by 8%–102%. Benefit–cost ratio (1.60–28.5) proved favourable to scale-up balanced nutrition. Better post-harvest soil health and residual benefits of sulfur, boron, and zinc up to four succeeding seasons indicated sustainability of the practice. Results showed that balanced nutrition is a way forward for sustainably improving farm productivity and livelihoods.